2021
DOI: 10.22207/jpam.15.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Two Virulent Phages to Combat Staphylococcus aureus and Enterococcus faecalis causing Dental Caries

Abstract: This study aimed to isolate and characterize bacteriophages, as a biocontrol agent, against certain antibiotic-resistant bacteria causing dental caries. Here, two dental caries-causing bacteria S. aureus and E. faecalis were isolated and characterized biochemically using the automated VITEK® 2 system. Antibiotic sensitivity pattern of the isolated dental caries bacteria was assessed against selection of antibiotics. The two isolates showed resistance against most of the tested antibiotics. To overcome this pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Several studies have demonstrated the importance of using bacteriophages against E. faecalis for the treatment of dental problems [ 33 , 34 , 37 , 38 ]. In the work by Nasr-Eldin et al [ 39 ], the isolated potential bacteria were identified biochemically, microscopically described using traditional techniques, and validated using the Vitek2 system. Over the past 30 years, antibiotic-resistant Enterococcus strains have become increasingly related to nosocomial infections, with increasingly high levels of antibiotic resistance and multidrug resistance [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the importance of using bacteriophages against E. faecalis for the treatment of dental problems [ 33 , 34 , 37 , 38 ]. In the work by Nasr-Eldin et al [ 39 ], the isolated potential bacteria were identified biochemically, microscopically described using traditional techniques, and validated using the Vitek2 system. Over the past 30 years, antibiotic-resistant Enterococcus strains have become increasingly related to nosocomial infections, with increasingly high levels of antibiotic resistance and multidrug resistance [ 40 ].…”
Section: Discussionmentioning
confidence: 99%